2012
DOI: 10.1007/s00216-012-6406-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin A 1–17 biotransformation in inflamed tissue, serum and trypsin solution analysed by liquid chromatography–tandem mass spectrometry

Abstract: Dynorphin A 1-17 (DYN A) is an endogenous neuropeptide that is of interest due to its diverse roles in analgesia, inflammation and addiction. Upon release, DYN A is subject to metabolism by a range of enzymes and its biotransformation is dependent on the site and environment into which it is released. In this study, we investigated the biotransformation of DYN A in rat inflamed tissue at pH 7.4 and 5.5, in rat serum and in trypsin solution. DYN A-porcine was incubated at 37 °C in each matrix over a range of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…Consistent with the abundant local accumulation of DYN 3-14 following biotransformation of DYN 1-17 in rodent inflamed tissue [6], this study has described a potential role for DYN 3-14 as an endogenous immune modulator in the tissue through modulation of pro-inflammatory cytokine release and the action upon TLR4-mediated NF-κB/p65 pathways.…”
Section: Lps-rs Derived Fromsupporting
confidence: 80%
See 3 more Smart Citations
“…Consistent with the abundant local accumulation of DYN 3-14 following biotransformation of DYN 1-17 in rodent inflamed tissue [6], this study has described a potential role for DYN 3-14 as an endogenous immune modulator in the tissue through modulation of pro-inflammatory cytokine release and the action upon TLR4-mediated NF-κB/p65 pathways.…”
Section: Lps-rs Derived Fromsupporting
confidence: 80%
“…In congruence with the lower potency exhibited by DYN 3-14, this peptide was produced abundantly following biotransformation of DYN 1-17 in rodent inflamed tissue homogenate [6]. Furthermore, DYN 3-14 does not undergo rapid degradation (93.40% remaining after 1 h, data not shown) upon incubation with THP-1 cells, suggesting that high local concentrations are present in the inflammatory milieu.…”
Section: Lps-rs Derived Frommentioning
confidence: 65%
See 2 more Smart Citations
“…Our group has demonstrated that dynorphin A 1-17 undergoes extensive and rapid biotransformation in an inflamed rat paw tissue homogenate, producing a unique set of dynorphin fragments [7]. It is likely that a similar set of fragments is produced from dynorphin released from leukocytes into inflamed tissue and that these dynorphin fragments mediate pain and inflammation.…”
Section: Introductionmentioning
confidence: 98%